Wave transport past slotted barriers - Ong, Mei Ling. (2009)
To assess the influence of oceanic waves on coastal areas, coastal engineers have done significant research and analysis of wave behaviour and coastal structure performance. Past researches have placed strong focus on behaviour of regular waves and on typical breakwaters such as caisson and rubble-mound types.